Avaliação dos efeitos farmacológicos e toxicológicos do estrato etanólico, fase clorofórmica e flavonoide de Praxelis clematidea (griseb.) R.M. King & H. Robinson (Asteraceae) - Oliveira Filho, Abrahão Alves de (2015)
The increasing resistance of micro-oganismos pathogens to existing antimicrobial market has driven the search for new therapeutic alternatives, such as natural herbal products belonging to various families of the plant kingdom, such as Asteraceae, which are presented as a viable solution due to the low cost and easy access of the population. However, the search for compounds derived from plants with pharmacological property must always be attached to toxicological studies in order to show the absence of these substances harm to the human body. Based on these premissias, pharmacological and toxicological effects of the ethanol extract (EPC), chloroform phase (FPC) and 5,7,4'-trimethoxyflavone (TMF) from Praxelis clematidea were studied. For the realization of in vitro antimicrobials studies was used the microdilution test with different fungal and bacterial strains. In carrying out studies of antioxidant activity and cytotoxicity was used human erythrocytes obtained from the blood bank of the University Hospital Lauro Wanderley. In acute toxicity studies and genotoxicity was used Swiss mice derived from the Vivarium Thomas George / UFPB. The experiments of antimicrobial activity revealed that EPC and FPC promoted an antifungal effect against Candida species, suggesting that both have secondary metabolites active against fungi. The TMF, major compound isolated from FPC, promoted an antibacterial effect against gram positive and gram negative species, with minimum inhibitory concentration (MIC) of 128 ug / mL and antifungal effect against different Candida species. The MIC TMF was 32 ug / ml for the strains of Candida krusei. With regard to the strains of Candida albicans, both the MIC and the minimum fungicidal concentration (MFC) was 64 ug / mL, combined with it, this involved the action antifungal effect on the cell wall and the plasma membrane of this species studied fungus. In addition, TMF caused decreased erythrocyte damage both by the exposure of hydrogen peroxide, as the osmotic change and showed an antioxidant effect against methemoglobin formation in erythrocytes. The TMF showed low theoretical toxicity and good oral bioavailability by in silico analysis. These data were confirmed by analyzing the cytotoxicity against erythrocytes, which showed hemolysis values below 10% for all blood types tested. In the evaluation of acute toxicity after oral administration of TMF (300 mg/kg), it can be seen that the test compound did not induce behavioral changes in mice and only alter feed intake of animals treated without altering body weight, organ weights and parameters biochemical and hematological evaluated. The analysis of the genotoxic potential of TMF showed that this metabolite was not able to damage the DNA of cells of the peripheral blood of treated animals. In conclusion, these results suggest that the EPC FPC and TMF have antimicrobial effect and which also has the flavonoid antioxidant effect with low cytotoxicity potency, toxicology and genotoxicity.